(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article analyzes one of the complex concept of modern religion – religious experience. Despite the sufficient sanctification of this phenomenon in the foreign theological religious science, the study of religious experience is unquenchable interest in both academic and diverse readership environment. In this article the author analyzes distribute in modern religious studies the concept of religious experience. However, attempts to apply the established methodology of the study and research of this phenomenon to a wider range of ethno-religious and religious traditions of the world. Passing through the prism of the religious traditions, religious experience becomes a specific manifestation. A person who has gone through this experience acquires a new dimension of his being.Comprehension of religious experience characteristic of different traditions helps a deeper understanding of how features of this or that religion, and the mentality of the individual. Key words: religion sacred, religious experience, the prophetic experience, mystic, mystical experience.